Malay-Chinese Interethnic Communication: An Analysis of Sensemaking in Everyday Experiences - Minah, Harun (2007)
This dissertation explores everyday communication patterns among ethnic Malays and Chinese in multicultural Malaysia. Specifically, the study examines communication strategies and the concept of sensemaking (Weick, 1969, 1979, 1995) in interethnic interpersonal communication processes. Because interethnic communication requires individuals, as social organisms (Blumer, 1969), to possess intercultural sensitivity (Condon & Yousef, 1975; Orbe, 1995), the notions of ethnicized knowledge and sensemaking in interactions involving different Asian groups merit further examination. In order to engage in this work, researchers must get inside the defining process of the socially diverse actors to further understand their symbolic (inter)actions (Blumer, 1969).